Transcriptomic Analysis of Menstrual Blood-Derived Stem Cells Transplantation Combined with Exercise Training in Promoting Spinal Cord Injury Recovery in Rats - QI Longju; CHEN Shiyuan; LIAO Zehua; SHI Yuanhu; SUN Yuyu; WANG Qinghua (Shiyan dongwu yu bijiao yixue)
ObjectiveTo explore the potential therapeutic targets and molecular mechanisms of menstrual blood-derived stem cells (MenSCs) transplantation combined with exercise training in promoting recovery in rats with spinal cord injury (SCI) through transcriptome sequencing analysis.MethodsFemale SD rats aged two months were selected and a SCI model was established by a hemisection at the tenth thoracic vertebra (T10). The rats were then divided into two groups: the Cell and Treadmill Training (CTMT) group, which received MenSCs transplantation and treadmill training after SCI, and the SCI group (control), with 12 rats in each group. One week after modeling, the CTMT group received a microinjection of 1×105 MenSCs at the injury site, followed by two weeks of weight-supported aerobic exercise training. Spinal cord tissue from the injury site was selected for transcriptome sequencing, and mRNA expression data from both the SCI and CTMT groups were analyzed. Differential gene expression, GO (Gene Ontology) functional enrichment, KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment, and protein-protein interaction (PPI) network analyses were performed. Motor function recovery was assessed using the Basso, Beattie, and Bresnahan (BBB) score, while histopathological changes at the injury site were evaluated through hematoxylin-eosin (HE) staining. Real-time fluorescent quantitative PCR and Western blotting were used to verify the expression of differentially expressed genes.ResultsTranscriptome sequencing analysis showed 247 upregulated genes and 174 downregulated genes in the CTMT group compared to the SCI group. Notably, genes such as Bdnf, Hmox1, Sd4, Mmp3, and Cd163 were significantly upregulated [|log2(FoldChange)|≥0.66, P<0.05]. KEGG pathway enrichment analysis and GO functional enrichment analysis indicated that these differentially expressed genes were mainly involved in growth and development, metabolic reactions, and immune-inflammatory processes, such as axon growth and the electron transport chain. The Bdnf gene was notably enriched in the PI3K-Akt signaling pathway. The BBB score showed that MenSCs transplantation combined with exercise training significantly improved the motor function of SCI rats. HE staining revealed that pathological changes at the injury site were significantly reduced in the treatment group. Furthermore, real-time quantitative PCR and Western blotting confirmed that brain-derived neurotrophic factor (BDNF) mRNA and protein expression levels in the CTMT group were significantly higher than those in the SCI group (P<0.001).ConclusionThe combined exercise training with MenSCs effectively promotes the recovery of motor function in SCI rats by upregulating BDNF expression, providing a novel strategy for SCI treatment.